One Year Facing COVID. Systematic Evaluation of Risk Factors Associated With Mental Distress Among Hospital Workers in Italy - Bonzini, Matteo; Comotti, Anna; Fattori, Alice; Cantù, Filippo; Colombo, Elisa; Tombola, Valentina; Myslymi, Eralda; Gatti, Michele; Stucchi, Giulia; Nava, Carlo; Bordini, Lorenzo; Riboldi, Luciano; et al. (Frontiers in Psychiatry, 2022)
Introduction Italy was the first Western country affected by the COVID-19 pandemic that still constitutes a severe challenge for healthcare workers (HCWs), with a deep impact on their mental health. Several studies confirmed that a considerable proportion of HCW developed adverse psychological impairment (PsI). To focus on preventive and rehabilitation measures, it is fundamental to identify individual and occupational risk factors. We systematically assessed possible PsI among all employees in a large university hospital in Italy, using validated psychometric scales in the context of occupational health surveillance. Methods In the period of July 2020 to July 2021, we enrolled 990 HCWs. For each subject, the psychological wellbeing was screened in two steps. The first-level questionnaire collected gender, age, occupational role, personal and occupational COVID-19 exposure, general psychological discomfort (GHQ-12), post-traumatic stress symptoms (IES-R), and anxiety (GAD-7). Workers showing PsI (i.e., test scores above the cutoff in at least one among GHQ-12, IES-R, and GAD-7) have been further investigated by the second-level questionnaire (psycho-diagnostic) composed by PHQ-9, DES-II, and SCL-90 scales. If the second-level showed clinically relevant symptoms, then we offered individual specialist treatment (third level). Results Three hundred sixteen workers (32%) presented signs of PsI at the first-level screening questionnaire. Women, nurses, and subjects engaged in the COVID-19 area and with an infected family member showed significantly higher PsI risk. PsI prevalence was strongly associated with the pandemic trend in the region but sensibly decreased after January 2021, when almost all workers received the vaccination. A proportion of subjects with PsI presented clinically relevant symptoms (second-level screening) on PHQ-9 (35%), DES (20%), and SCL-90 (28%). These symptoms were associated neither to direct working experience with patients with COVID-19 nor to COVID-19 experience in the family and seemed not to be influenced by the pandemic waves or workers vaccination. Conclusions The evaluation of psychological wellbeing of all hospital workers, directly or indirectly exposed to pandemic consequences, constitutes a unique condition to detect individual, occupational, and non-occupational risk factors for PsI in situations of high stress and/or disasters, as well as variables associated with symptom chronicization.